Vietnam : For travellers by travellers - McDonald, Stuart; Karalus, Danielle (Australia Tales from the other side, 1995)
Contents: history; culture; country; general; before you arrive; how to get into and out of Vietnam; getting around in Vietnam; Hanoi; around Hanoi; Northeast Vietnam; far northern Vietnam; Northwest Vietnam; North central Vietnam; central Vietnam; south central Vietnam; central highlands; Vietnamese south coast; Ho Chi Minh city; around Ho Chi Minh city; Mekong delta,...
Includes index
Keywords: Quản trị DV Du lịch và Lữ hành